Surface Strategy Taxonomy on EFL Learners’ Academic Presentation: A Study of Grammatical Error Analysis - Nurdin Nurdin; Umi Hani (Doctoral Program of Social Science Pasundan University, 2026)
This study investigates grammatical errors produced by EFL learners during oral academic presentations by applying the Surface Strategy Taxonomy proposed by Heidi Dulay, Marina Burt, and Stephen Krashen (1982). The objectives of this research are to identify the types of grammatical errors found in students’ academic presentations, analyze the possible sources of the errors, and determine the most frequently occurring grammatical error type. This study employed a descriptive qualitative research design. The participants of this study were 20 third-semester students of the English Department at Universitas Pamulang. The data were collected through video recordings of students’ oral academic presentations and were analyzed using the framework of Error Analysis proposed by Stephen Pit Corder (1967). The findings revealed that the students produced four types of grammatical errors based on the Surface Strategy Taxonomy, namely omission, addition, misformation, and misordering. A total of 94 grammatical errors were identified in the students’ presentations. Misformation errors were found to be the most dominant type with 39 occurrences (41.49%), followed by omission errors with 28 occurrences (29.79%), addition errors with 17 occurrences (18.09%), and misordering errors with 10 occurrences (10.63%). The study also revealed that the grammatical errors were mainly caused by interlingual interference and intralingual interference. Interlingual interference occurred because students transferred Indonesian grammatical patterns into English expressions, while intralingual interference resulted from incomplete understanding and overgeneralization of English grammatical rules. Based on the findings, it can be concluded that EFL learners still experience difficulties in applying correct grammatical structures during spontaneous oral academic communication. Therefore, greater emphasis on grammar application in speaking activities is necessary to improve students’ grammatical accuracy and academic speaking performance Keywords: Academic Presentation, Grammatical Errors Analysis, Surface Strategy Taxonomy